Cases and materials on the English legal system - Zander, Michael 1932- (Law in context, 2007)
This title, a companion volume to The Law Making Process, is the definitive collection of cases and materials on the workings of the English legal system. Written by the foremost scholar in the field, it surveys how the law functions from the trial process (from pre-trial proceedings to the funding of trials), the role of the jury, and the legal profession. This edition takes account of all recent major legislative and judicial changes and updates the material on the established areas of the law. The book takes a 'law in context' approach, setting out those factors beyond the legal environment which impact on and inform the changes within it. The collection is required reading for all students seeking a thorough knowledge and in-depth understanding of how the English legal system operates